MELD score as a predictor of mortality, length of hospital stay, and disease burden: A single-center retrospective study in 39, 323 inpatients. Issue 24 (June 2017) - Roth, Jan A.; Chrobak, Carl; Schädelin, Sabine; Hug, Balthasar L.
Abstract : Abstract: The laboratory-based model for end-stage liver disease (MELD) score reflects the function of the kidney, liver, and extrinsic coagulation pathway and might be used as a general prognostic tool for the assessment of patients. We therefore aimed to investigate a potential association of the MELD score with mortality, length of hospital stay (LOS), and disease burden in a general patient population. We performed a retrospective observational study at a tertiary referral center. From January 2012 through December 2013, all consecutive inpatients aged 18 years were eligible for the study; patients with missing MELD parameters on hospital admission and/or treatments influencing the international normalized ratio, that is, novel oral anticoagulants and vitamin K antagonists, were excluded. The MELD score on hospital admission was calculated retrospectively. The primary outcome measure was in-hospital all-cause mortality; secondary outcome measures were LOS and the number of comorbidities. A total of 39, 323 inpatients were included in the final analysis. On admission, MELD scores of 15 to 19, 20 to 29, and ≥30 points (reference <15 points) showed increased hazard ratios (HRs) for in-hospital mortality in uni- and multivariable analysis with an adjusted HR of 2.52 (95% confidence interval [CI], 1.81–3.49; P  < .001), 2.70 (95% CI, 1.89–3.84; P  < .001), and 8.00 (95% CI, 3.91–16.39; P  < .001), respectively. Increased MELD scores of 15 to 19, 20 to 29, and ≥30 points were positively associated with LOS and the number of comorbidities in uni- and multivariable analysis. In our study population consisting of adult inpatients, the MELD score on hospital admission was significantly associated with mortality, LOS, and the number of comorbidities. We suggest to prospectively validate the MELD score in inpatients as part of clinical decision support systems. Abstract : Supplemental Digital Content is available in the text